2015
DOI: 10.3109/14756366.2015.1014475
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolo[1,5-a]quinazoline scaffold as 5-deaza analogue of pyrazolo[5,1-c][1,2,4]benzotriazine system: synthesis of new derivatives, biological activity on GABAA receptor subtype and molecular dynamic study

Abstract: To investigate the binding affinity of GABAA receptor subtype, new pyrazolo [1,5-a]quinazolines were designed, synthesized, and in vitro evaluated. These compounds, 5-deaza analogues of pyrazolo[5,1-c][1,2,4]benzotriazine derivatives which were already studied in our research group, permit us to evaluate the relevance of the nitrogen or the oxygen atom at 5-position of the tricyclic scaffold. Molecular dynamic study was done on a set of the new and known ligands to rationalize and to explain the lack of affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…24 Moreover, very interesting is the evidence that the α4 and α5subunits are expressed in airway smooth muscle (ASM), therefore this GABA A -R subtypes represent a compelling pharmacological target to achieve bronchodilation in asthma, and both α4 and α5 GABA A -R positive allosteric modulators could be able to relax precontracted ASM. 25,26 Continuing our study on GABA A -Rs subtype ligands, in our previous work, we synthesized a series of compounds with pyrazolo[1,5-a]quinazoline (PQ) 27 scaffold as 5-deaza analogues of the pyrazolo[5,1-c][1,2,4]benzotriazines (PBT), endowed with anxiolytic, antihyperalgesic, 18,28 or procognitive activity, 21 Chart 1. In the new 5-deaza-scaffold, the disubstitution at 3,4 or 3,5 positions gave compounds lacking of receptorial recognition, and the only compound exhibiting binding affinity is the ethyl pyrazolo[1,5-a]quinazoline 3carboxylate 27 showing a completely aromatized tricyclic system.…”
mentioning
confidence: 99%
“…24 Moreover, very interesting is the evidence that the α4 and α5subunits are expressed in airway smooth muscle (ASM), therefore this GABA A -R subtypes represent a compelling pharmacological target to achieve bronchodilation in asthma, and both α4 and α5 GABA A -R positive allosteric modulators could be able to relax precontracted ASM. 25,26 Continuing our study on GABA A -Rs subtype ligands, in our previous work, we synthesized a series of compounds with pyrazolo[1,5-a]quinazoline (PQ) 27 scaffold as 5-deaza analogues of the pyrazolo[5,1-c][1,2,4]benzotriazines (PBT), endowed with anxiolytic, antihyperalgesic, 18,28 or procognitive activity, 21 Chart 1. In the new 5-deaza-scaffold, the disubstitution at 3,4 or 3,5 positions gave compounds lacking of receptorial recognition, and the only compound exhibiting binding affinity is the ethyl pyrazolo[1,5-a]quinazoline 3carboxylate 27 showing a completely aromatized tricyclic system.…”
mentioning
confidence: 99%
“…Despite the presence, in this new series, of substituents already identified for the 8-PQ [19] and for pyrazolo [5,1-c] [1,2,4]benzotriazine [22,23], as important to form hydrogen bond interaction (oxygen atom of methoxy or benzyloxy group) or to form π-π interactions with lipophilic area in the receptor (iodine or arylalkylester moiety), the movement of these substituents from position 8 to position 6 is detrimental for binding. On the other hand, our previous study of the pyrazoloquinazoline system clearly showed that also the introduction of substituents at position 5 led to the loss of binding recognition [18].…”
Section: Resultsmentioning
confidence: 88%
“…Continuing our study on GABA A -Rs subtype ligands, we focalized our attention on compounds with pyrazolo [1,5-a] quinazoline (PQ) scaffold as 5-deaza analogues of the potent pyrazolo [5,1-c] [1,2,4]benzotriazines, previously identified by our research group as high affinity GABA A -R subtype ligands [10,13,16,17]. We first synthesized pyrazolo[1,5-a]quinazoline and 4,5-dihydropyrazolo [1,5-a] quinazoline variously substituted at 3-position and/or 8-position [18,19]. The most interesting compounds showing K i values in the (sub)nanomolar range (0.27-34 nM) were the 8-methoxypyrazolo[1,5-a]quinazoline 3-(hetero)arylester derivatives, both in the dehydro form and in the dihydro form.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend is verified also in the 3‐triazole derivatives ( 18a and 21a ). All these molecules will be inserted in a next study of molecular dynamic to evaluate the occurrence of hydrogen bonds and Van der Walls interactions, between the ligand and the amino acids of receptor protein .…”
Section: Resultsmentioning
confidence: 99%